First-ever ischemic stroke and increased risk of incident heart disease in older adults. (14th April 2020) - Sposato, Luciano A.; Lam, Melody; Allen, Britney; Richard, Lucie; Shariff, Salimah Z.; Saposnik, Gustavo
Abstract : Objective: Poststroke cardiac complications are common. It is unknown whether the reason is shared risk factors and preexisting heart disease or stroke-associated myocardial and coronary injury. We tested the hypothesis that first-ever ischemic stroke is associated with increased risk of incident cardiovascular complications in patients without known preexisting cardiac comorbid conditions. Methods: This population-based cohort study included residents in Ontario between 2002 and 2012 who were ≥66 years of age without known cardiovascular disease. We compared the incident risk of major adverse cardiovascular events (MACE), defined as myocardial infarction, unstable angina, congestive heart failure, coronary artery disease, coronary artery revascularization, or cardiovascular death, at 1 year in patients with first-ever ischemic stroke vs propensity-matched individuals without stroke (4:1 matching using 31 variables). To estimate cause-specific hazard ratios (HRs), we used Cox regression models adjusted for variables with weighted standardized differences >0.10 or known to influence the risk of MACE. Results: We included 21, 931 patients with first-ever ischemic stroke and 71, 696 propensity-matched individuals, well balanced on all variables used for propensity matching. First-ever ischemic stroke was associated with increased unadjusted incident MACE risk (HR 4.5, 95% confidence interval [CI] 4.3–4.8). MACE adjusted risk was highest in the first 30 days (HR 25.0, 95% CI 20.5–30.5) and declined both at 31 to 90 days (HR 4.8, 95% CI 4.1–5.7) and at 91 to 365 days (HR 2.2, 95% CI 2.0–2.4). Conclusions: In this large population-based study, ischemic stroke was independently associated with increased risk of incident MACE. Whether this association is explained by stroke-associated cardiac injury, preexisting subclinical cardiovascular comorbid conditions, or both remains unknown.